Exploring augmented reality integration for enhancing heritage museum exhibits: a focus on innovative display design - Yanxue, Zhang; Abdul Aziz, Faziawati; Abu Bakar, Nor Azlina; Xinyi, Zhang; Jijiang, Zhang (Human Resource Management Academic Research Society, 2024)
As custodians of human civilization, heritage museums embody irreplaceable cultural treasures, inherently constrained by the imperative of preservation and the fixed attributes of their exhibits, which often limit their restoration efforts and aesthetic appeal. Nevertheless, the advent of augmented reality technology injects a newfound vitality into the realm of heritage museums. This paper seeks to harness the potential of augmented reality technology to propose innovative approaches to the exhibition design of heritage museums, aiming to elevate the visitor experience by offering diverse and enriched ways of accessing information. Through a user-centric lens, this research explores the myriad possibilities that augmented reality technology introduces to museum display design, particularly in reimagining spatial arrangements. By seamlessly integrating various forms (3D, 2D, audio, text) and content types (history, art), the paper envisions fostering interactive engagements between visitors and artifacts. The overarching goal is to augment the ornamental value of cultural relics, transcending traditional constraints and providing a versatile array of possibilities for the presentation of cultural heritage.